Pengaruh Kompensasi, Komunikasi dan Lingkungan Kerja terhadap Kinerja Karyawan PT Swadharma Sarana Informatika Cabang Luwuk: The Influence of Compensation, Communication and Work Environment on Employee Performance at PT Swadharma Sarana Informatika, Luwuk Branch - Kamaru, Sri Mulyaningsih; Milang, Ichsan; Musa, Nuzran (Jurnal Ilmiah Produktif, 2025)
This study aims to determine the Influence of Compensation, Communication and Work Environment on Employee Performanceat PT Swadharma Sarana Informatika Luwuk Branch, Data collection techniques include questionnaires and interviews. The sampleused was 11 respondents. The analysis tools used are multiple linear regression, correlation coefficient, determination coefficient, Ttest and F test. From the results of the partial test analysis (T test), namely the Compensation variable (X1), the t-value of the calculation of the X1 variable = 2.232 > table = 1.943 with a probability value level of 0.002, partial testing (T test), namely theCommunication variable (X2), the t-value calculates the variable X 2 = 3.009 > t table = 1.943 with a probability value level of0.001, Partial testing (T test) is a variable of Work Environment (X3), the t-value calculates the variable (X3) = 5.694 > t table =1.943 with a probability value of 0.001 and judging from the calculation of the F test = 17.244 > table F = 4.35 with a significanceof 0.001 it can be known that the sum of F is greater than the table F so that the hypothesis that it is suspected that Compensation(X1), Communication (X2) and Work Environment (X3) simultaneously or together have a significant influence on EmployeePerformance (Y) in PT Swadharma Informatics Tool Luwuk Branch.